2003
DOI: 10.1073/pnas.0630290100
|View full text |Cite
|
Sign up to set email alerts
|

The high variance of AMPA receptor- and NMDA receptor-mediated responses at single hippocampal synapses: Evidence for multiquantal release

Abstract: Most of our knowledge about transmission at central synapses has been obtained by studying populations of synapses, but some important properties of synapses can be determined only by studying them individually. An important issue is whether a presynaptic action potential causes, at most, a single vesicle to be released, or whether multiquantal transmission is possible. Previous work in the CA1 region has shown that the response to stimulation of a single axon can be highly variable, apparently because it is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
63
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 44 publications
(65 reference statements)
6
63
2
Order By: Relevance
“…Individual Schaffer collateral synapses have been documented to produce up to 40 pA of current (Conti and Lisman, 2003), but the number of active AMPARs in our model spine (supplemental Table 1, available at www.jneurosci.org as supplemental material) is still higher than most previous estimates (Matsuzaki et al, 2001;Nimchinsky et al, 2004). When we tuned our model, we used only data from spines that did produce sizable calcium transients in current clamp.…”
Section: Discussioncontrasting
confidence: 40%
“…Individual Schaffer collateral synapses have been documented to produce up to 40 pA of current (Conti and Lisman, 2003), but the number of active AMPARs in our model spine (supplemental Table 1, available at www.jneurosci.org as supplemental material) is still higher than most previous estimates (Matsuzaki et al, 2001;Nimchinsky et al, 2004). When we tuned our model, we used only data from spines that did produce sizable calcium transients in current clamp.…”
Section: Discussioncontrasting
confidence: 40%
“…However, the criteria by which single synapses are selected in minimal stimulation experiments will reject those that release more than a single vesicle. In contrast, optical measurements of NMDA receptor-mediated calcium transients in single spines suggested that potency increases with P r , arguing in favor of MVR (Oertner et al, 2002;Conti and Lisman, 2003). Theoretically, these results could be also explained by enhanced spillover from neighboring release sites (Barbour and Häusser, 1997;Rusakov and Kullmann, 1998) or perhaps fusion pore regulation that controls the rate of transmitter release (Choi et al, 2000;Renger et al, 2001).…”
Section: Discussionmentioning
confidence: 73%
“…It is generally agreed that an increase in the P r occurs during facilitation; however, it is still debated whether the increase in P r is solely responsible for the facilitation or whether postsynaptic modifications also take place. Several studies reported an exclusive presynaptic alteration (Gulyas et al, 1993;Stevens and Wang, 1995;Dobrunz and Stevens, 1997;Hanse and Gustafsson, 2001;Silver et al, 2003;Chen et al, 2004;Lawrence et al, 2004), but evidence has also been published supporting significant postsynaptic modifications, including an increased quantal size after multivesicular release (Oertner et al, 2002;Conti and Lisman, 2003) or removing the polyamine block from certain postsynaptic glutamate receptors (Rozov and Burnashev, 1999). To some extent, the reason for the discrepancy is likely attributable to differences in experimental approaches, such as the preparations, the age of the animals, and the identity of the synapses examined.…”
Section: Discussionmentioning
confidence: 82%
“…This led to the formulation of the one-vesicle hypothesis (Korn et al, 1994): either no vesicle or only one vesicle is released at one release site after the arrival of a presynaptic action potential. Several recent studies tested the one-release site, one-vesicle hypothesis at mammalian central synapses and came to various conclusions (Auger et al, 1998;Wadiche and Jahr, 2001;Oertner et al, 2002;Schneggenburger et al, 2002;Conti and Lisman, 2003) (but see Gulyas et al, 1993;Stevens and Wang, 1995;Dobrunz and Stevens, 1997;Hanse and Gustafsson, 2001;Silver et al, 2003;Lawrence et al, 2004). As mentioned above, the discrepancy may be the consequence of technical differences, most notably distinctions in the way presynaptic axons were stimulated.…”
Section: Discussionmentioning
confidence: 98%